Pengaruh Penguatan Profil Pelajar Pancasila terhadap Pembentukan Karakter Siswa pada Mata Pelajaran IPS di Madrasah Aliyah Alkhairat Bolangitang Barat - Riska Pohontu; Melizubaida Mahmud; Agil Bahsoan; Hasiru, Roy; Ardiansyah Ardiansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of strengthening the Pancasila Student Profile on the development of students' character in Social Science (IPS) subjects at Madrasah Aliyah Alkhairat Bolangitang Barat. Strengthening the Pancasila Student Profile has become a key focus in the implementation of the Merdeka Curriculum, which emphasizes the development of values such as religiosity, mutual cooperation, creativity, independence, global diversity, and critical thinking in students. This research uses a quantitative approach with a survey method, distributing questionnaires to 57 students. Data analysis was performed using simple linear regression with the help of SPSS to determine the contribution of the Pancasila Student Profile Strengthening variable (X) to students' character development (Y). The results show the regression equation Ŷ = 53.782 + 0.586X, indicating that every 1% increase in variable X will raise variable Y by 0.586. The positive regression coefficient indicates a significant and positive relationship between the two variables. The R Square value of 0.533 suggests that 53.3% of the variation in students' character is explained by strengthening the Pancasila Student Profile, while 46.7% is influenced by other factors outside the study. Thus, it can be concluded that the implementation of the Pancasila Student Profile Strengthening program plays an important role in improving students' character in IPS learning.